Measurement of thermography parameters for field application/ Mohd Murshid Jamaludin - Jamaludin, Mohd Murshid (2000)
Thennography is only at it prehminary stage and it has potential to be developed in Malaysia. It is a technique of obtaining an image of the beat distribution over the surface of material. It is also one of the techniques so-called Non-Destructive Testing (NDT) which is harmless to the object being studied. The intensity of emitted radiation reveals bidden defect where it is depends on the temperature of the object and the ability of the objects to radiate. The infrared camera records the temperature contrast and produces a colorful image and temperature profiles can be constructed from it. Specific parameters such as emissiviry e, theanal conductivity kr thermal effusivity e, thermal diflusrviiy a and density p, has to be taken account in obtaining the temperature measurements, in this study, ThermaCAM PM595 infrared camera with accuracy ± 2°C and ± 2% is used to measure the temperature of sample with different of sample emissivity, coated sample and size of defect at ambient temperature and at indoor and outdoor field application. The samples analyzed were in various surface conditions scanned by ThermaCAM PM595 infrared camera that give emissiviry reading.